Knockdown of long noncoding RNA CCDC144NL-AS1 attenuates migration and invasion phenotypes in endometrial stromal cells from endometriosis†. Issue 4 (28th November 2018) - Zhang, Chen; Wu, Wei; Zhu, Honglan; Yu, Xiaoming; Zhang, Yinli; Ye, Xue; Cheng, Hongyan; Ma, Ruiqiong; Cui, Heng; Luo, Jianjun; Guan, Jing; Chang, Xiaohong
Abstract: Endometriosis (EM) is a mysterious and complicated disease that has been found to be multifactorial. Recent studies demonstrated that long noncoding RNAs (lncRNAs) play an important role in the pathogenesis of EM. However, the functional and biological mechanisms of lncRNAs in EM remain unknown. Here, we performed microarray analyses to compare the lncRNA expression profiles of four paired ectopic endometrial (EC) tissues and eutopic endometrial (EU) tissues from patients with ovarian EM. A novel lncRNA, CCDC144NL-AS1, was identified as being potentially functional. CCDC144NL-AS1 expression was upregulated in EC tissues compared to EU and normal endometrial (NE) tissues. Its expression was higher in EC tissues than in EU tissues in 86.7% (26/30) of patients with EM. Despite the lack of a significant increase according to revised American Fertility Society (rAFS) stages, approximately 60% of stage VI EM cases exhibited higher CCDC144NL-AS1 levels, many more than in the stage II–III cases. Subcellular fractionation demonstrated that CCDC144NL-AS1 was localized in the cytoplasm and nucleus of the human EM-derived immortalized endometrial stromal cell line hEM15A. CCDC144NL-AS1 depletion suppressed the migration and invasion of hEM15A cells, but exerted no effects on cell adhesion, proliferation, apoptosis, or cell cycle. Knockdown of CCDC144NL-AS1 dramatically altered the distribution of cytoskeletal filamentous actin (F-actin) stress fibers compared to the negative control group treatment. Western blot analysis revealed that knockdown of CCDC144NL-AS1 attenuated the protein levels of vimentin filaments and MMP-9, but not N-cadherin or β-catenin. Collectively, our results suggest that CCDC144NL-AS1 might be involved in the pathogenesis of EM and provide a novel target for ovarian EM. Abstract : Elevated lncRNA CCDC144NL-AS1 levels contribute to cytoskeleton reorganization, migration, and invasion in endometrial stromal cells via regulating vimentin and MMP-9.